Acute renal failure following chorioamnionitis - Gurung, G; Rana, A (Journal of Institute of Medicine Nepal, 2008)
Case report: Renal failure is a rare entity encountered in obstetrics commonly found as complication of septic abortion, severe PIH, APH and PPH and rarely as a result of hyperemesis gravidarum, chorio-amnionitis (1%) and idiopathic postpartum renal failure. Chorio- amnionitis is a frequent occurrence as a result of premature rupture of membrane, however acute renal failure is unusual consequence of chorio-amnionitis. We are presenting this case of renal failure as a result of chorioamnionitis because of its rarity in the obstetric practice. Key words: Renal failure, chorioamnionitis, premature rupture of membrane The full text of this paper is available at Journal of Institute of Medicine website